Accelerated recovery after surgery in pediatric urology: current evidence and future practice in Kazakhstan (Bangladesh Journal of Medical Science, 2026)
Background pediatric urology has seen significant advancements, particularly with the adoption of enhanced recovery after surgery (eras) protocols, which aim to improve recovery outcomes. These protocols, initially developed for adult surgeries, have been adapted for pediatric urology with promising results. However, challenges related to healthcare infrastructure and cultural factors in kazakhstan may affect their implementation and effectiveness. Aim this study evaluates the impact of eras protocols on postoperative recovery in pediatric urology surgeries in kazakhstan, focusing on recovery times, opioid use, complication rates, and patient satisfaction. Methods a prospective observational study was conducted at three pediatric urology centers in kazakhstan between january 2023 and december 2024. A total of 300 patients, aged 1-18 years, undergoing elective urologic surgery were divided into pre-eras (n=150) and post-eras (n=150) cohorts. Key postoperative metrics, including hospital length of stay (los), opioid use, time to oral intake, and time to mobilization, were compared between the two groups. Results the eras cohort demonstrated significantly improved recovery outcomes, with reduced hospital los (2.8 vs. 4.5 days, p